A Comparison of Resident Procedure Logs to Data Generated from an Electronic Health Record - Smith, Moira E.; Layng, Timothy A. (ACI Open, 2023)
Background Emergency medicine (EM) residents are required to report procedural competency, often in a database separate from the electronic health record (EHR), in a redundant and time-consuming manner. We hypothesize that, if documented in an appropriate manner, procedural reports generated from an EHR reliably exceed those required by the Accreditation Council for Graduate Medical Education (ACGME) as well as those self-reported by EM residents.Objectives (1) To compare the number of medical resuscitations recorded in the EHR to the number documented by residents in a separate database. (2) To compare the number of medical resuscitations recorded in the EHR to the ACGME requirement for graduation.Methods Self-reported numbers of adult medical resuscitation by each resident of the previous three graduating classes of one EM program were compared with those generated from the EHR (Epic Systems, Verona, Wisconsin). There is no discrete documentation of medical resuscitations in the EHR. The ACGME describes a resuscitation as “…patient care for which prolonged physician attention is needed,” and thus, a surrogate was determined to be any patient for which the attending physician documented critical care time.Results Data generated from the EHR reliably exceeded reported (mean [M] = 165.78, standard deviation [SD] = 45.97) and required (M = 188.09, SD = 30.93) numbers for adult medical resuscitations for 100% of the residents of the past three graduating classes (n = 32).Conclusion In an accredited EM residency program that utilizes a modern EHR with a validated reporting functionality, residents should not need to redundantly log the number of adult medical resuscitations performed. Each resident in this study performed significantly more adult medical resuscitations than they logged and more than required by the ACGME, and thus, the time spent documenting these in a separate database was superfluous. Furthermore, this process increases resident awareness of proper documentation and data stewardship, two skills certain to prevail throughout their careers as modern EM physicians.
Keywords: electronic health records and systems; databases; data creation and storage; emergency medicine; training and education requirements; data collection